Comparative study of intravenous iron sucrose versus intravenous ferric carboxymaltose in the management of iron deficiency anaemia in pregnancy - Khatun, Ferdousi; Biswas, Chandralekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Iron deficiency anaemia is the most common anaemia with significant effect over health status. It is a major hematological, nutritional deficiency but manageable health problem among the pregnant women. Anaemia during pregnancy is associated with increased morbidity and mortality of pregnant women and their developing foetuses. In pregnant women, oral iron is often used for prophylaxis and is recommended as first-line treatment for iron deficiency anaemia in pregnancy. Intravenous (i.v.) iron preparations provide greater and more rapid repletion of iron stores than oral iron. Methods: This is a prospective, single center, comparative interventional randomized hospital based study carried among antenatal mother admitted in antenatal ward in the department Obstetrics and Gynaecology, Medical college and hospital, Kolkata from 1st January 2019 to 30th June 2020 (one and half year duration), comprised of 180 pregnant women divided two groups. Group- A (90) received ferric carboxymaltose (FCM), group- B (90) received iron sucrose. All pregnant women between 16 to 34 weeks of gestation with iron deficiency anaemia with hemoglobin values between 7-10 gm%, were counselled and included. Medical eligibility criteria were used for client selection. Results: In FCM group 3 week post treatment hemoglobin level was 9.87±0.77 and in iron sucrose group it was 9.39±0.72 (p=0.001). 6 week post treatment hemoglobin level in FCM group was 11.51±0.76 and in iron sucrose group it was 10.78±0.61 (p=0.001). Mean change in hemoglobin in FCM group after 3 week post treatment was 1.51±0.63 and after 6 week it was 3.15±0.79. In iron sucrose group at 3 week it was 1.16±0.43 and at 6 week it was 2.55±0.52. The mean change in hemoglobin level was higher among patients of FCM compared to Iron sucrose group. Conclusions: Ferric carboxymaltose was safer and more efficient in treatment of iron deficiency anaemia in pregnant women as compared to iron sucrose with lesser adverse effect and better patient compliance.